Evaluation of Fraud Prevention Policies in the National Health Insurance System in Indonesia: Narrative Literature Review - Putri Galuh Inggi; Anhari Achadi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Fraud in the National Health Insurance System (JKN) in Indonesia is a serious issue that harms health services and financing. Fraud practices such as phantom billing and diagnosis manipulation threaten the goals of the National Health Insurance (JKN) to provide fair and quality health access. The latest data shows significant losses due to fraud, with a report by the Corruption Eradication Commission revealing the discovery of fraud amounting to IDR 35 billion in three hospitals. To address this issue, the Minister of Health Regulation Number 16 of 2019 is expected to enhance the management and accountability of the JKN Fund, while also encouraging more effective policy evaluation. Objective: This research aims to evaluate the effectiveness of fraud prevention policies in the National Health Insurance System in Indonesia. Method: This research employs a narrative literature review approach, starting with the inclusion of the keywords